Managerial Knowledge Spillovers from FDI Through the Diffusion of Management Practices. - Fu, X (2012)
This paper analyses the nature and extent of managerial knowledge spillovers from foreign direct investment through the diffusion of modern management practices and provides the first empirical evidence regarding their size and transmission mechanisms using establishment-level panel data from the UK. The paper finds that there are significant vertical and horizontal spillovers of management practices from foreign to local firms. The analysis suggests that vertical spillovers within supply chains are the most effective transmission channel. However, we have not find robust evidence suggesting the reverse spillovers of management practices from local to foreign firms.